Efektivitas Media Game Geometry Maze Untuk Meningkatkan Kemampuan Pemecahan Masalah Pada Siswa Sekolah Dasar - Rizky Nur Hidayah; Wahyudi (LPPM Universitas Buana Perjungan Karawang, 2020)
The purpose of this research is to know about the effectiveness of geometry maze games media on problem skills in elemantary school students. This research is a pre-experimental using in group, pretest and posttest desaign. Data collection method is interview, questionnaire, and test. The effectiveness of media from maze games seen from the results of the pretest and posttest problem solving ability by means of a test Paired SamplesT-Test with helped by SPSS 25.0 for windows. The results is significant value (2-tailed) equals 0,000 pretest and posttest. From Paired Samples T-Test game geometry maze media towards probleam solving skilss